The Education System in Mexico - M. Posner, C. (UCL Press, 2018)
Over the last three decades, a significant amount of research has sought to relate educational institutions, policies, practices and reforms to social structures and agencies. A number of models have been developed that have become the basis for attempting to understand the complex relation between education and society. At the same time, national and international bodies tasked with improving educational performances seem to be writing in a void, in that there is no rigorous theory guiding their work, and their documents exhibit few references to groups, institutions and forces that can impede or promote their programmes and projects. As a result, the recommendations these bodies provide to their clients display little to no comprehension of how and under what conditions the recommendations can be put into effect. The Education System in Mexico directly addresses this problem. By combining abstract insights with the practicalities of educational reforms, policies, practices and their social antecedents, it offers a long overdue reflection of the history, effects and significance of the Mexican educational system, as well as presenting a more cogent understanding of the relationship between educational institutions and social forces in Mexico and around the world.